1990
DOI: 10.1111/j.1399-3054.1990.tb09048.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid and indole‐3‐butyric acid regulation of maturation and accumulation of storage proteins in somatic embryos of interior spruce

Abstract: The ontogenetic course followed by somatic embryos of interior spruce is highly dependent on the media concentration of abscisic acid (ABA). Little or no organized development occurs in the absence of ABA and as the level of ABA is increased, a range of embryo types is produced. “Shooty embryo” structures predominate in many callus lines at low levels of ABA (1‐10 μM), while 10‐20 μM ABA promotes the formation of bipolar embryos that germinate precociously. When ABA is increased to 30‐40 μM, precocious germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(62 citation statements)
references
References 30 publications
(30 reference statements)
4
56
0
2
Order By: Relevance
“…The higher the ABA concentration, the greater the number of mature embryos. A similar result was reported in Pinus strobus (Klimaszewska and Smith, 1997), Picea glauca-engelmannii complex (Roberts et al, 1990a), and P. glauca . The addition of AC into the media notably enhanced the maturation efficiency, with around a 4-fold enhancement achieved by using 33.3 to 100 µM in combination with 2 gL -1 AC.…”
Section: Maturation Of Somatic Embryossupporting
confidence: 88%
See 2 more Smart Citations
“…The higher the ABA concentration, the greater the number of mature embryos. A similar result was reported in Pinus strobus (Klimaszewska and Smith, 1997), Picea glauca-engelmannii complex (Roberts et al, 1990a), and P. glauca . The addition of AC into the media notably enhanced the maturation efficiency, with around a 4-fold enhancement achieved by using 33.3 to 100 µM in combination with 2 gL -1 AC.…”
Section: Maturation Of Somatic Embryossupporting
confidence: 88%
“…Somatic embryos of the hybrid larch (Larix x leptoeuropaea) developed normally on a medium supplemented with 60 µM ABA, but abnormally on a medium with no ABA (Gutmann et al, 1996). Most of the studies on somatic embryogenesis in conifers have reported ABA as a key hormone in embryo development and that the number and quality of embryo produced was vastly reduced in its absence (Durzan and Gupta, 1987;von Arnold and Hakman, 1988;Hakman and von Arnold, 1988;Attree and Fowke, 1993;Dunstan et al, 1998 Several authors have suggested that the role of ABA in somatic embryogenesis is to inhibit cleavage polyembryony with the consequent development of individual somatic embryos (Durzan and Gupta, 1987;Boulay et al, 1988;Krogstrup et al, 1988;Gupta et al, 1991), to stimulate the accumulation of nutrients, lipids, proteins, and carbohydrates , and suppress precocious germination (Roberts et al, 1990a). In addition, Gupta et al (1993) reported improved desiccation tolerance to less than 10% water content with 80 to 90% germination rates in Norway spruce embryos produced with a combination of ABA and AC.…”
Section: Effect Of Kind and Concentration Of Sugarmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations would suggest that development and germination of somatic embryos is promoted by ABA. Stimulation of the development of somatic embryos by ABA has recently been observed in a variety of species including Brassica, Datura, Nicotiana (Sethi et al 1990), Hordeum (Rengel & Jelaska 1986), Picea (Dunstan et al 1988;Roberts et al 1990)), Pinus (Sen et al 1989), Medicago (Fujii et al 1990) and Triticum (Brown et al 1989;Qureshi et al 1989). There is growing evidence that ABA directly controls the gene expression of embryogenesis proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of abscisic acid (ABA) on somatic embryo production and plant regeneration was studied because this plant growth regulator has been shown to have a promotive effect on somatic embryo development and maturation (e.g. Dunstan et al 1988;Brown et al 1989;Qureshi et al 1989;Fujii et al 1990;Roberts et al 1990) and shoot regeneration (Rengel & Jelaska 1986;Qureshi et al 1989;Sen et al 1989;Sethi et al 1990) for a range of species.…”
Section: Introductionmentioning
confidence: 99%